MODEL RANTAI NILAI USAHA UNTUK MENINGKATKAN NILAI TAMBAH BERKELANJUTAN PADA UKM FILLET TUNA DI KOTA KENDARI - Sarini Yusuf; Nurdiana A Nurdiana A (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2016)
The aims of this study to improve business margin and added value for tuna Fillets businesses in Kendari, by identify the early models of the value chain business of tuna Fillet that use the Participatory Rural Appraisal (PRA). The results showed that (1) factors that become problems in the development of the business value chain tuna Fillets in Kendari are : (a) the quality and price of raw materials which are varied for each region tuna fish suppliers, (b) raw materials  from outside the city of Kendari very vulnerable to contracting the bacteria; (c) the quantity of raw material supply fluctuates widely, depending on weather conditions; (d) the length of the production process is not consistent; (e) increased production costs often occur; (f) the quality of labor is not adequate; and (g) some equipment are only available outside the city of Kendari; (2) a source of raw materials obtained from the three regions namely Kendari, Bau-Bau and Wakatobi; (3) tuna Fillet production process is carried out through six stages; (4) Marketing location are Kendari, Denpasar, Surabaya and Jakarta City, while overseas markets are Singapore, Japan and Australia.Keywords : Value Chain, Market, Margin, Tuna Fish, Value Added